2021
DOI: 10.3390/ijerph182412964
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes among Teachers and Trainers Working with Adolescents

Abstract: Previous scientific literature has not determined the influence exerted by trainers and teachers of adolescents on the development of gender stereotypes in sport. For this reason, the aims of the present research were to establish differences in gender stereotypes in sport among teachers and trainers as a function of profession and sex and to analyze the influence of age and years of experience of male and female trainers and teachers on the gender stereotypes in sport. For this purpose, 127 teachers and train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…In fact, they preferred to carry out the main task first, and then assess the students' performance through the modified games. Although this finding coincides with Iranian studies (Salehi Omran et al, 2015) indicating the dominance of teacher-based teaching methodology, it is still suggested that Iranian teachers should gradually reduce their role as the main lynchpin of education while using NCD guidelines for teaching game/sports in different grades, and create more cognitive challenges for students by engaging them in exploration and problem solving from the beginning to the end of the session (Kirk, 2010).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In fact, they preferred to carry out the main task first, and then assess the students' performance through the modified games. Although this finding coincides with Iranian studies (Salehi Omran et al, 2015) indicating the dominance of teacher-based teaching methodology, it is still suggested that Iranian teachers should gradually reduce their role as the main lynchpin of education while using NCD guidelines for teaching game/sports in different grades, and create more cognitive challenges for students by engaging them in exploration and problem solving from the beginning to the end of the session (Kirk, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Given that the PE curriculum in Iranian schools seeks to strengthen the components of knowledge, skills and attitudes of students, Iranian PE teachers have shown interest in Game-Based Approaches (GBAs). Contrary to traditional teaching approaches in which learners first learn techniques in isolation and then generalize them to the context of the game (Kirk, 2010), in GBAs, tactical awareness should be learnt before technical skills through the use of game-like situations. Although increased motivation in learning and achievement has been reported in Iran as a result of applying this pedagogical approach (Alimohammadi et al, 2017;Mohammadi et al, 2019), it seems that students learn more skills than tactics (Salehi Omran et al, 2015) because PE teachers often struggle with GBAs in teaching PE (Katoozian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the promotion of physical activity in this population has become a critical necessity, even more so after the COVID-19 pandemic, in which physical activity was made impossible, at the same time that adolescent screen time increased (Bates et al, 2020;Castañeda-Babarro et al, 2020;Dubuc et al, 2021).…”
Section: Gonzálezmentioning
confidence: 99%
“…In this regard,Mateo-Orcajada et al (2023) found that mobile apps such as Strava, Pacer, MapMyWalk or Pokémon Go were useful for achieving changes in body composition effectiveness of their use in this population. This is due to the fact that the research designs proposed have important limitations(Mateo-Orcajada, Vaquero-Cristóbal, et al, 2023c), with the mobile applications being used in reduced time periods, such as weekends…”
mentioning
confidence: 99%